Respon Masyarakat Kudus Terhadap Asuransi Syariah - M. Arif Hakim (State Institute of Islamic Studies (IAIN) Salatiga, 2012)
The purpose of this reseach is: (1) How is the response of Kudus society to Syariah insurance; (2) What are the main factors which influence the response of Kudus society to Syariah insurance. This reseach including field reseach with approach qualitative. Data analiysis using descriptive analysis. Result of this reseach indicate that response of Kudus society to Syariah insurance is very good. The main factors which influence the response is factor endogenous and exogenous. Factor endogenous us including prosperity, mount the earnings, life style and custom. Exogenous factor is products of syariah insurance, strat from and closing limit, mount the premium rate, specific things and draw other govermental regulation, and other rule or raxation.